Effect of Crystalloid Administration Timing on Hypotension in Spinal Anesthesia for Cesarean Delivery: Preload Versus Coload: A Study at a Tertiary Care Hospital in Rawalpindi - Talha Rehman Zahid; Rashk-e- Hinna; Usama Farooq; Adnan Arshad Waraich; Rubina Bashir; Irfan Ali (Life and Science)
Objective: To assess and compare the occurrence of hypotension and the demand for vasopressors in parturients undertaking spinal anesthesia during cesarean delivery, distinguishing between those who received crystalloid preload and those who received coload. Study Design: Quasi-experimental study. Place and Duration of Study: The study was conducted at Department of Anesthesiology, Combined Military Hospital (CMH) Rawalpindi, Pakistan for two years from July 2021 to July 2023. Methods: Fifty-four parturients, categorized as ASA II, with full-term singleton gestations planned for elective cesarean delivery under spinal anesthesia, were randomly divided into two groups. Both groups received 15ml/kg of crystalloid as a preload and a coload. The initial readings of heart rate and arterial pressures were evaluated before spinal induction and subsequently at one minute intervals until the completion of the operation. Intravenous ephedrine was administered to manage hypotension, characterized by a more than 20% reduction in systolic blood pressure. Results: The group receiving preload demonstrated notably lower values in both the minimum recorded systolic and mean blood pressure, as well as in the reduction of systolic and mean blood pressure from the baseline, in comparison to the coload group (P < 0.001). The occurrence of hypotension in the preload group was significantly elevated at 92.6%, indicating a statistically significant difference (P = 0.039) when compared to the coload group, where the incidence was 67%. Additionally, the mean ephedrine dose requirement was significantly higher in the preload group at 12.2 ± 5.9 mg (P = 0.029) compared to the coload group, which had a mean ephedrine dose requirement of 8.3 ± 6.8 mg. There were no significant differences between neonatal outcomes, such as APGAR score and blood gases, between the two groups. Conclusion: The adoption of the crystalloid coload method proved more effective than the preload technique in reducing the incidence of intraoperative maternal hypotension and decreasing the necessity for vasopressors in parturients undergoing cesarean delivery.